2016
DOI: 10.1097/ajp.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

The SPADE Symptom Cluster in Primary Care Patients With Chronic Pain

Abstract: Objectives Sleep disturbance, pain, anxiety, depression and low energy/fatigue, the SPADE pentad, are the most prevalent and co-occurring symptoms in the general population and clinical practice. Co-occurrence of SPADE symptoms may produce additive impairment and negatively affect treatment response, potentially undermining patients' health and functioning. The purpose of this paper is to determine: (1) prevalence and comorbidity (i.e., clustering) of SPADE symptoms; (2) internal reliability and construct vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 39 publications
8
35
0
Order By: Relevance
“…10 This symptom cluster is similar to that of cytokine-induced sickness behavior studied in animal models 9 and more recently has been documented in human clinical populations. 16 One possibility is that pro-inflammatory modulation of CNS processes play a role in the expression of these symptoms.…”
Section: Introductionsupporting
confidence: 65%
“…10 This symptom cluster is similar to that of cytokine-induced sickness behavior studied in animal models 9 and more recently has been documented in human clinical populations. 16 One possibility is that pro-inflammatory modulation of CNS processes play a role in the expression of these symptoms.…”
Section: Introductionsupporting
confidence: 65%
“…Such an observation has given rise to the study of symptom clusters (Miaskowski, Dodd, & Lee, 2004) A common symptom cluster observed within the context of primary care is composed of sleep disturbance, pain, anxiety, depression, and low energy/fatigue (SPADE) (Davis, Kroenke, Monahan, Kean, & Stump, 2016). In this study of 250 patients with musculoskeletal pain, only 9.6% were monosymptomatic while 20% of the sample had all 5 symptoms in the SPADE cluster.…”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnosmentioning
confidence: 99%
“…For example, the co‐occurrence of pain and depression ranges from 30% to 50%, and several prospective studies have shown bidirectional relationships between pain, insomnia, fatigue, and emotional distress . Although treatment of an individual symptom can be complicated by co‐occurrence of other symptoms (eg, pain modifying the response to depression treatment), interventions that improve overall symptom burden are associated with subsequent improvement in patient‐reported functioning . Taken together, optimal patient‐centered care requires the assessment and management of multiple co‐occurring symptoms.…”
mentioning
confidence: 99%
“…[5][6][7][8] Although treatment of an individual symptom can be complicated by co-occurrence of other symptoms (eg, pain modifying the response to depression treatment 9 ), interventions that improve overall symptom burden are associated with subsequent improvement in patient-reported functioning. 10,11 Taken together, optimal patient-centered care requires the assessment and management of multiple cooccurring symptoms.…”
mentioning
confidence: 99%